Penentuan Harga Jual Produk dengan Menggunakan Metode Cost Plus Pricing dan Mark Up Pricing Pada CV. Tumou Pratama - Chriseva Voerman (Universitas Sam Ratulangi, 2023)
The success of the company in achieving the targeted profit cannot be separated from the role of good management and being able to make company strategies, one of which is the selling price. Determining the selling price based on costs in the simplest form, namely the cost plus pricing method and the mark up pricing method. The cost plus pricing method is a method in the form of a company approach to be able to determine the selling price of a unit product where this selling price can cover all costs. The mark up pricing method is a method that is generally used by traders whose business is to buy and resell the goods after other costs have been added. The purpose of this study was to determine the right selling price for the company CV. Tumou Pratama is engaged in the wooden house industry by comparing the cost plus pricing method and the mark up pricing method. The method used is descriptive qualitative research method. Based on the research results, the selling price for the large type and the extra type in the cost plus pricing method and the mark up pricing method is higher than the company's selling price. This is not only because the company still calculates a small amount of desired profit, the company also does not calculate the cost per type of wooden house where each process of making wooden house products has a different cost from other types. Keywords: Selling Price, Cost Plus Pricing, Mark Up Pricing